Experimental study on the fuel requirements for the thermal degradation of bodies by means of open pyre cremation. (June 2018) - Yermán, Luis; Wall, Harrison; Carrascal, Jerónimo; Browning, Aidon; Chandraratne, Devduni; Nguyen, Christina; Wong, Andy; Goode, Tristan; Kyriacou, Daniel; Campbell, Margaret; Cao, Julian; Do, Tam; et al.
Abstract: The results of a systematic study of open pyre cremation of bodies is reported here with the aim of providing quantitative information on the mechanisms controlling the cremation process and the relationship between the characteristics of a fire and the level of consumption of a body. Systematically constructed timber pyres and recently euthanized pig carcasses (as surrogates for human bodies) were used to establish the importance of fuel quantity, methodology of fuel application, body size and body arrangement. The results indicate that a fuel/body mass ratio greater than 9 is necessary to overcome the endothermic effect of the body on the pyre. Even with a fuel/body mass ratio of 9 and ideal burning conditions full destruction of all organic matter could not be attained. Highlights: The characteristics of a wood pyre that can fully consume a body were studied. Systematically constructed pyres and pig carcasses, as human surrogate, were used. Ideally, a ratio dry wood/body of 5 is necessary to achieve complete destruction. In practice, a ratio higher than 9 is necessary to achieve complete destruction.